Controlling and Fine-Tuning Charge-Transfer Emission in 2,6-Dicyanoaniline Multichromophores Prepared through Domino Reactions: Entry to a Potentially New Class of OLEDs - Plass, Fabian; Bönisch, Simon; Held, Felix; Ullrich, Tobias; Fischer, Florian; Guryev, Anton; Görling, Andreas; Kahnt, Axel; Tsogoeva, Svetlana (Journal of Organic Chemistry, 2021)
Substituted 2,6-dicyanoanilines are versatile electron donor-acceptor compounds, which have recently received considerable attention, since they exhibit strong fluorescence and may have utility in the synthesis of fluorescent materials, non-natural photosynthetic systems, and materials with nonlinear optical properties. The majority of known synthetic procedures are, however, "stop-and-go"reaction processes involving time-consuming and waste-producing isolation and purification of product intermediates. Here, we present the synthesis of substituted 2,6-dicyanoanilines via atom-economical and eco-friendly one-pot processes, involving metal-free domino reactions, and their subsequent photochemical and photophysical measurements and theoretical calculations. These studies exhibit the existence of an easily tunable radical ion pair-based charge-transfer (CT) emission in the synthesized 2,6-dicyanoaniline-based electron donor-acceptor systems. The charge-transfer processes were explored by photochemical and radiation chemical measurements, in particular, based on femtosecond laser photolysis transient absorption spectroscopy and time-resolved emission spectroscopy, accompanied by pulse radiolysis and complemented by quantum chemical investigations employing time-dependent density-functional theory. This chromophore class exhibits a broad-wavelength-range fine-tunable charge recombination emission with high photoluminescence quantum yields up to 0.98. Together with its rather simple and cost-effective synthesis (using easily available starting materials) and customizable properties, it renders this class of compounds feasible candidates as potential dyes for future optoelectronic devices like organic light-emitting diodes (OLEDs).
CRIS-Team Scopus Importer:2021-05-14

Controlling the Charge Transfer Mechanism and Efficiency by Means of Different C70 Regioisomeric Adducts - Plass, Fabian; Lukyanov, Daniil A.; Konev, Alexander S.; Kahnt, Axel; Amsharov, Konstantin; Khlebnikov, Alexander F.; Guldi, Dirk Michael (Small Structures, 2020)
Here, differences stemming from two newly synthesized electron donor–acceptor conjugates, α- or β-regioisomeric adducts featuring orthogonal arrangements of an electron-donating free-base porphyrin (H2P) and electron-accepting C70, are reported. Key to a full-fledged investigation in terms of both experiments and theory is the use of a rigid linker to separate the electron acceptor and donor. Both conjugates are experimentally investigated by means of femtosecond/nanosecond transient absorption measurements, which is further supported by radiation chemical studies based on pulse radiolysis. Significant regioisomeric differences are seen in the charge recombination kinetics, in general, which are as large as 1.4-fold, and in the relative distributions of the charge recombination pathways, in particular, which reach nearly 1.5-fold. Clearly, α-regioisomers of C70 adducts are much better suited for the construction of future energy conversion systems than β-regioisomers; a fact that relates to the superior electron delocalization within the carbon caps of C70 made out of “corannulenoid” fragments relative to the equator region of fullerenes featuring extended “phenanthrenoid” rings.<br
Keywords: fullerenes; molecular electron donor–acceptors; photoinduced electron transfers; regioisomers; synthetic methods

Effect of the triazole ring in zinc porphyrin-fullerene dyads on the charge transfer processes in NiO-based devices - Nikolaou, Vasilis; Plass, Fabian; Planchat, Aurelien; Charisiadis, Asterios; Charalambidis, Georgios; Angaridis, Panagiotis A.; Kahnt, Axel; Odobel, Fabrice; Coutsolelos, Athanassios G. (Physical Chemistry Chemical Physics, 2018)
Herein, the synthesis of three covalently linked donor-acceptor zinc porphyrin-fullerene (ZnP-C-60) dyads (C(60)trZnPCOOH, C(60)trZnPtrCOOH and C60ZnPCOOH) is described, and their application as sensitizers in NiO-based dye-sensitized solar cells (DSCs) is discussed. To the best of our knowledge, this is the first example where covalently linked ZnP-C-60 dyads have been used as chromophores in NiO-based DSCs. In an effort to examine whether the distance of the chromophore from the electron acceptor entity and/or the NiO surface affects the performance of the cells, a triazole ring was introduced as a spacer between ZnP and the two peripheral units C-60 and -COOH. The triazole ring was inserted between ZnP and C-60 in dyad C(60)trZnPCOOH, whereas both the anchoring group and C-60 were connected to ZnP through triazole spacers in C(60)trZnPtrCOOH, and dyad C60ZnPCOOH did not contain any triazole linker. Photophysical investigation performed by ultrafast transient absorption spectroscopy in solution and on the NiO surface demonstrated that all the porphyrin-fullerene dyads exhibited long-lived charge-separated states due to electron shifts from the reduced porphyrin core to C-60. The transient experiments performed in solution showed that the presence of triazole ring influenced the photophysical properties of the dyads C(60)trZnPCOOH and C(60)trZnPtrCOOH and in particular, increased the lifetime of the charge-separated states compared to that of the C60ZnPCOOH dyad. On the other hand, the corresponding studies on the NiO surface proved that the triazole spacer has a rather moderate impact on the charge separation (NiO-ZnP center dot+-C-60(center dot-)) and charge recombination (NiO-(3)*ZnP-C-60) rate constants. All three dyads exhibited enhanced performance in terms of photovoltaic measurements with more than threefold increase compared to the reference compound PhtrZnPCOOH in which the C-60 acceptor is absent. Two different electrolytes were examined (I-3(-)/I- and Co-III/II) and in most cases, the presence of the triazole ring enhanced their photovoltaic performance. The best performing dyad in I-3(-)/I- was C(60)trZnPCOOH (PCE = 0.076%); in Co-III/II, the best performing dyad was C(60)trZnPtrCOOH (PCE = 0.074%).
Created from Fastlane, WoS look-up

Efficient charge-transfer from diketopyrrolopyrroles to single-walled carbon nanotubes - Papadopoulos, Ilias; Menon, Arjun; Plass, Fabian; Molina, Desire; Harreiß, Christina; Kahnt, Axel; Spiecker, Erdmann; Sastre-Santos, Angela; Guldi, Dirk Michael (Nanoscale, 2021)
In this contribution, the excited state charge-transfer interactions between single-walled carbon nanotubes (SWCNTs) and a variety of phenyl, 4-bromophenyl, and thiophene substituted diketopyrrolopyrroles (DPPs), is described. Atomic force microscopy (AFM) and aberration corrected high resolution transmission electron microscopy (AC-HRTEM) corroborated the successful formation of DPP/SWCNTs. Steady-state absorption, fluorescence, and Raman spectroscopies all gave insights into the impact on their ground and excited states as well as on the nature of their electronic communication/interaction. Of great value was time-resolved transient absorption spectroscopy on the femto- and nanosecond time-scales; it assisted in deciphering the charge-transfer mechanism from the DPPs to the SWCNT and in analyzing the dynamics thereof with transfer efficiencies of up to 81%. Important confirmation for the one-electron oxidized DPPs came from pulse radiolysis assays with focus on establishing their spectral fingerprints. Our full-fledged work demonstrates that the successful preparation of stable DPP/SWCNTs represents an important step towards establishing them as a viable alternative to porphyrin-based systems in emerging applications such as solar energy conversion.
CRIS-Team WoS Importer:2021-07-16

Interfacing tetrapyridyl-C-60 with porphyrin dimers via -conjugated bridges: artificial photosynthetic systems with ultrafast charge separation - Stangel, Christina; Plass, Fabian; Charisiadis, Asterios; Giannoudis, Emmanouil; Chararalambidis, Georgios; Karikis, Kostas; Rotas, Georgios; Zervaki, Galateia E.; Lathiotakis, Nektarios N.; Tagmatarchis, Nikos; Kahnt, Axel; Coutsolelos, Athanassios G. (Physical Chemistry Chemical Physics, 2018)
We report on the synthesis, characterization and photophysical properties of a donor-bridge-acceptor supramolecular hybrid system, consisting of a tetrapyridyl fullerene derivative (C-60-tpyr) as electron acceptor, with the four pyridyl groups as part of oligophenyleneethynylene/phenylenevinylene bridges, and zinc porphyrin dimers (ZnP)(2) as electron donor species. Based on the metal-to-ligand coordination between the zinc metal centers of (ZnP)(2) and the four pyridyl entities of C-60-tpyr, a strong binding constant (5 x 10(5) M-1) for the formation of C-60-tpyr[(ZnP)(2)](2) was evidenced. Insights into the electronic interactions between the photoactive (ZnP)(2) units and C-60-tpyr emanated from complementary physicochemical assays, which were further supported by theoretical calculations. Notably, the absorption and emission titration assays revealed strong interactions between the electron donor and acceptor species within C-60-tpyr[(ZnP)(2)](2), both in the ground and excited state. Moreover, femtosecond and nanosecond laser photolysis transient absorption measurements were performed and provided solid evidence for intramolecular electron transfer processes derived from the singlet excited state of (ZnP)(2) to C-60-tpyr. Comparison with systems in which either four monomeric zinc porphyrins (ZnP) were complexed with C-60-tpyr or a (ZnP)(2) was coordinated with a dipyridylfullerene revealed the beneficial role of C-60-tpyr in increasing the lifetime of charge-separation.
Created from Fastlane, WoS look-up

Long-Living Holes in Grey Anatase TiO2 Enable Noble-Metal-Free and Sacrificial-Agent-Free Water Splitting - Liu, Ning; Mohajernia, Shiva; Nguyen, Nhat Truong; Hejazi, Seyedsina; Plass, Fabian; Kahnt, Axel; Yokosawa, Tadahiro; Osvet, Andres; Spiecker, Erdmann; Guldi, Dirk Michael; Schmuki, Patrik (Chemsuschem, 2020)
Titanium dioxide has been the benchmark semiconductor in photocatalysis for more than 40 years. Full water splitting, that is, decomposing water into H2 and O2 in stoichiometric amounts and with an acceptable activity, still remains a challenge, even when TiO2-based photocatalysts are used in combination with noble-metal co-catalysts. The bottleneck of anatase-type TiO2 remains the water oxidation, that is, the hole transfer reaction from pristine anatase to the aqueous environment. In this work, we report that “grey” (defect engineered) anatase can provide a drastically enhanced lifetime of photogenerated holes, which, in turn, enables an efficient oxidation reaction of water to peroxide via a two-electron pathway. As a result, a Ni@grey anatase TiO2 catalyst can be constructed with an impressive performance in terms of photocatalytic splitting of neutral water into H2 and a stoichiometric amount of H2O2 without the need of any noble metals or sacrificial agents. The finding of long hole lifetimes in grey anatase opens up a wide spectrum of further photocatalytic applications of this material.
CRIS-Team Scopus Importer:2020-08-21
Keywords: long-living holes; noble-metal-free; sacrificial-agent-free; titanium dioxide; water splitting

Synthesis and Photophysical Properties of a Sc3N@ C80‐Corrole Electron Donor–Acceptor Conjugate - Liu, Bin; Fang, Hongyun; Li, Xiaofang; Cai, Wenting; Bao, Lipiao; Rudolf, Marc; Plass, Fabian; Fan, Louzhen; Lu, Xing; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
Embedding endohdedral metallofullerenes (EMFs) into electron donor–acceptor systems is still a challenging task owing to their limited quantities and their still largely unexplored chemical properties. In this study, we have performed a 1,3-dipolar cycloaddition reaction of a corrole-based precursor with Sc3N@C80 to regioselectively form a [5,6]-adduct (1). The successful attachment of the corrole moiety was confirmed by mass spectrometry. In the electronic ground state, absorption spectra suggest sizeable electronic communications between the electron acceptor and the electron donor. Moreover, the addition pattern occurring at a [5,6]-bond junction is firmly proven by NMR spectroscopy and electrochemical investigations performed with 1. In the electronically excited state, which is probed in photophysical assays with 1, a fast electron-transfer yields the radical ion pair state consisting of the one-electron-reduced Sc3N@C80 and of the one-electron-oxidized corrole upon its exclusive photoexcitation. As such, our results shed new light on the practical work utilizing EMFs as building blocks in photovoltaics.<br
Keywords: corroles; donor–acceptor systems; fullerenes; metallocycles; photophysics

Synthesis and Photo/Radiation Chemical Characterization of a New Redox-Stable Pyridine-Triazole Ligand - Al-Romema, Abdulaziz; Plass, Fabian; Nizovtsev, Alexey; Kahnt, Axel; Tsogoeva, Svetlana (ChemPhysChem, 2024)
Photocatalysis using transition-metal complexes is widely considered the future of effective and affordable clean-air technology. In particular, redox-stable, easily accessible ligands are decisive. Here, we report a straightforward and facile synthesis of a new highly stable 2,6-bis(triazolyl)pyridine ligand, containing a nitrile moiety as a masked anchoring group, using copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click reaction. The reported structure mimics the binding motif of uneasy to synthesize ligands. Pulse radiolysis under oxidizing and reducing conditions provided evidence for the high stability of the formed radical cation and radical anion 2,6-di(1,2,3-triazol-1-yl)-pyridine compound, thus indicating the feasibility of utilizing this as a ligand for redox active metal complexes and the sensitization of metal-oxide semiconductors (e. g., TiO2 nanoparticles or nanotubes).
CRIS-Team Scopus Importer:2024-08-02
Keywords: click chemistry; laser photolysis; pulse radiolysis; pyridine-triazole; redox-stable ligand

Using OpenBIS as Virtual Research Environment: An ELN-LIMS Open-Source Database Tool as a Framework within the CRC 1411 Design of Particulate Products - Plass, Fabian; Englisch, Silvan; Apeleo Zubiri, Benjamin; Pflug, Lukas; Spiecker, Erdmann; Stingl, Michael (Data Science Journal, 2023)
The digital transformation and consequent use of new digital technologies not only have a substantial impact on society and companies, but also on science. Analog documentation as we have known it for centuries will eventually be replaced by intelligent and FAIR (Findable, Accessible, Interoperable, and Reusable) systems. In addition to the actual research data and results, metadata now plays an important role not only for individual, independently existing projects, but for future scientific use and interdisciplinary research groups and disciplines as well. The solution presented here, consisting of an electronic laboratory notebook and laboratory information management system (ELN-LIMS) based on the openBIS (open Biology Information System) environment, offers interesting features and advantages, especially for interdisciplinary work. The Collaborative Research Centre (CRC) 1411 ‘Design of Particulate Products’ of the German Research Foundation is characterized by the cooperation of different working groups of synthesis, characterization, and simulation, and therefore serves as a model environment to present the implementation of openBIS. OpenBIS, as an open source ELN-LIMS solution following FAIR principles, provides a common set of general entries with the possibility of sharing and linking (meta-)data to improve the scientific exchange between all users.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Databases; ELN-LIMS; Interdisciplinary work; Open Science; Research data management